2017
DOI: 10.2172/1349212
|View full text |Cite
|
Sign up to set email alerts
|

A Manufacturing Cost and Supply Chain Analysis of SiC Power Electronics Applicable to Medium-Voltage Motor Drives

Abstract: NREL prints on paper that contains recycled content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…However, high-purity SiC powder, which can be used to grow SiC boules, is only available from a limited number of suppliers, and is relatively expensive [25]. At present, the United States is the global leader in the production of SiC substrates and wafers, followed by Europe and Japan.…”
Section: High-temperature Componentsmentioning
confidence: 99%
“…However, high-purity SiC powder, which can be used to grow SiC boules, is only available from a limited number of suppliers, and is relatively expensive [25]. At present, the United States is the global leader in the production of SiC substrates and wafers, followed by Europe and Japan.…”
Section: High-temperature Componentsmentioning
confidence: 99%
“…Furthermore, such analysis helps determine if the increased costs associated with widebandgap devices, specifically SiC, could be overcome by the increased performance enabled by SiC capabilities. In [1], Horowotiz et al demonstrated, through a bottoms-up model that the savings from space and cooling in a SiC-based 1-MW variable-frequency drive resulted in an overall drive cost similar to the current industry standards. In order to understand and judge the cost benefits associated with the proliferation of widebandgap based photovoltaic (PV) inverters, it is necessary to model their MSP as well as determine the levelized cost of energy (LCOE) if such inverters were to be used in widespread grid integration of PV systems.…”
Section: Introductionmentioning
confidence: 99%
“…Stoke's shifts for V − Si defects remain on the order of 10 meV [16]. Furthermore, the bulk material properties of SiC make it more amenable than diamond to high-voltage, high-power, and high-temperature applications and it is also more promising as a long-term candidate material due to its physical durability [17], engineering flexibility [18], and increasingly inexpensive manufacturing cost [19,20]. One disadvantage is that the optically detected magnetic resonance of V − Si SiC has a lower visibility compared to that of the (NV) − center in diamond, but this too is being overcome [21].…”
Section: Introductionmentioning
confidence: 99%